As causativas sintéticas do português brasileiro de acordo com o modelo minimalista - Glenda Aparecida Queiroz Milanio (2014)
The goal of this work is to analyze synthetic causative structures formed from transitive verbs in contemporary Brazilian Portuguese. In the present research, we have used the studies of Chomsky (1981, 1999, 2002) until recent developments in Generative Theory (Pylkkänen,2002, 2008; Blanco, 2010, 2011). Regarding the semantic representation of these structures, we described the necessary criteria for recognition of synthetic causatives. For this description, we adopted a verbal classification based on the cognitive structure of the mind(Stillings et al., 1995), in which we proposed three verb classes: sensory verbs, processing verbs, and motor verbs of the first and second orders. Based on this classification, we recognize that synthetic causatives are usually formed from motor transitive verbs of the second order. These verbs, besides being related to the motor system, require an alienable artificial instrument for the realization of the verbal action. In this perspective, the synthetic causative express an ambiguous reading with respect to the external argument, since this canbe interpreted as agent or patient of the action. Thus, the ambiguity concerning the executing agent of the verbal action and the fact that the alienable artificial instrument can be transferredfrom one individual to another are necessary criteria for synthetic causatives. In relation to the syntactic representation of these structures, we consider that synthetic causatives formed fromtransitive verbs are derived from an underlying analytic structure. Thus, we adopt the functional heads Voice and v CAUSE with light verb, proposed by Pylkkänen (2002, 2008) and reviewed by Blanco (2010, 2011) to develop our proposal. Therefore, we assume that thesynthetic causative possesses two vPs and two VoicePs in its structure. The higher vP CAUSE in the syntactic tree projects the verb make, which is not phonologically realized, while the lower vP projects the transitive verb. The higher VoiceP introduces the external argument ofthe verb make, and the lower VoiceP hosts a DP proarb, allowing the interpretation of an indefinite subject.